Benefits and obstacles of e-portfolios in elementary education: Documentingthe students’ perspective - Iolie Nicolaidou (My University, 2012)
This paper is a documentation of the students’ perspective on the integration of an innovative e-portfolio tool into the Cyprus Language Arts primary education curriculum for the first time. The participants were twenty fourth-grade students who systematically used a weblog based e-portfolio tool (WordPress) designed, repurposed and localized into Greek, over one academic year. Data sources included a student-questionnaire on students’ perceptions of e-portfolios, the researcher’s field notes and nine videotaped student interviews. The data analysis, which followed an inductive grounded theory approach, revealed benefits and limitations of both the e-portfolio implementation process and the tool itself. Based on students’ perceptions, both instructional design modifications and suggestions on improving the pedagogy behind the use of e-portfolios are suggested. These will help to overcome identified limitations and make the Wordpress e-portfolio tool a useful tool for primary education in different languages.
Keywords: Students' Attitudes; E-Portfolios; Primary Education